The Effects of Free Heme on Functional and Molecular Changes During Ex Vivo Normothermic Machine Perfusion of Human Kidneys - Hosgood, Sarah A.; Elliott, Tegwen R.; Jordan, Nina P.; Nicholson, Michael L. (Frontiers in Immunology, 2022)
Normothermic machine perfusion (NMP) is a technique of kidney preservation designed to restore cellular metabolism after cold ischaemia. Kidneys are perfused with an oxygenated banked red blood cell (RBC) based solution for 1h at 36°C. During NMP, RBCs can become damaged, releasing free heme into the perfusate. This can act as a damage-associated molecular pattern (DAMP) activating inflammatory signalling pathways. The aim of this study was to measure the levels of free heme during NMP and assess the effect on kidney function and determine any association with inflammatory and stress related gene expression. Levels of free heme were measured in perfusate samples from a series of donation after circulatory death (DCD) kidneys undergoing NMP as part of a randomised controlled trial (RCT). The age of RBCs and levels of free heme were correlated with perfusion parameters. Changes in gene expression were analysed in a series of kidneys declined for transplantation using the NanoString nCounter Organ Transplant Panel and qRT-PCR. Older units of RBCs were associated with higher levels of free heme and levels increased significantly during NMP (Pre 8.56 ± 7.19µM vs 26.29 ± 15.18µM, P<0.0001). There was no association with levels of free heme and perfusion parameters during NMP (P > 0.05). Transcriptional and qPCR analysis demonstrated the upregulation of differentially expressed genes associated with apoptosis (FOS and JUN), inflammatory cytokines (IL-6, SOCS3, ATF3), chemokines (CXCL8, CXCL2, CC3/L1) and oxidative stress (KLF4) after NMP. However, these did not correlate with levels of free heme (P >0.05). A significant amount of free heme can be detected in the perfusate before and after NMP particularly when older units of red cells are used. Although transcriptional analysis demonstrated significant upregulation of genes involved with apoptotic, inflammatory and oxidative pathways these were not associated with high levels of free heme.